"Listening Literacies" as Keys to Rebuilding Trust in Journalism: A Typology for a Changing News Audience. (4th July 2021) - Robinson, Sue; Jensen, Kelly; Dávalos, Carlos
ABSTRACT: Using in-depth interviews and textual analyses of trust-building projects as case studies, this research explores the links between trust and news literacy. The major contribution includes a contextualized definition and formal typology for the literacies to come out of these initiatives and programs, which are well-funded by foundations, technology companies and others. In these trust-building strategies, we are asked to reimagine who is responsible for information literacy so that mainstream journalism can be revitalized. Four dimensions of news literacy for trust-building in public information exchange emerged from this dataset: civic consumption, amateur (co-)production (sharing), professional information production (newsrooms), and algorithms/technology. We find that the notion of a "listening literacy" within these strategies has application for not only K-12 schools, universities and "regular" people, but also for journalists and media platforms to restore trust in accurate information.